2004
DOI: 10.1017/s0265021504000353
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lidocaine on neutrophil CD11b/CD18 and endothelial ICAM-1 expression and IL-1β concentrations induced by hypoxia–reoxygenation

Abstract: Lidocaine at clinically relevant concentrations decreased neutrophil CD18 and endothelial ICAM-1 expression but not endothelial IL-1beta concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…IL-1 also activates production of other cytokines, such as IL-6, IL-8 and TNF [2]. Several reports have suggested that Lid has anti-inflammatory action, such as suppression of proinflammatory cytokine production [15], suppression of histamine release from basophiles and mast cells [31], attenuation of monocyte chemoattractant protein-1 production and reduction of chemotaxis [17]. Therefore, our results suggest that Lid might be useful not only as a local anesthetic but also as an anti-inflammatory drug in cows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-1 also activates production of other cytokines, such as IL-6, IL-8 and TNF [2]. Several reports have suggested that Lid has anti-inflammatory action, such as suppression of proinflammatory cytokine production [15], suppression of histamine release from basophiles and mast cells [31], attenuation of monocyte chemoattractant protein-1 production and reduction of chemotaxis [17]. Therefore, our results suggest that Lid might be useful not only as a local anesthetic but also as an anti-inflammatory drug in cows.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports suggested that LAs reduce the phagocytosis, chemotaxis, adhesion molecule expression, and production of superoxides of granulocytes [11,13,15,24]. It has also been reported that LAs reduce the lymphocyte blast transformation and cytokine secretion of mononuclear cells [6,25,29].…”
mentioning
confidence: 99%
“…In addition, lidocaine can reduce the expression of endothelial adhesion molecules in epithelial cells, endothelial cells and neutrophils and could thereby inhibit neutrophil adhesion and migration (Lan et al 2004). In rats with experimentally induced obstructive ileus, IV administration of lidocaine prevents fluid secretion into the lumen of the small intestine and reduces edema formation in the intestinal wall (Nellgard et al 1996).…”
Section: Lidocainementioning
confidence: 99%
“…These include interactions with and alterations of functions in host neutrophils and macrophages. For instance, lidocaine was found to affect functions such as chemotaxis, phagocytosis, superoxide anion and lysosomal enzyme release as well as pro-and anti-inflammatory cytokines production by neutrophils [9][10][11] . Similarly, the anti-inflammatory properties of lidocaine have been shown to be effective in the treatment of LPS-induced ALI.…”
Section: Introductionmentioning
confidence: 99%